Combined electric accumulation unit for air heating - Tikhomirov, Dmitry; Dudin, Stepan; Trunov, Stanislav; Rastimeshin, Sergey; Tikhomirov, Anatoly; Kuzmichov, Alexey (Revista de la Universidad del Zulia, 2019)
The article describes the functional-technological scheme of an energy-efficient combined electric accumulation heating system for agricultural production facilities. A distinctive feature and novelty is the use of direct and accumulative heating. They presented the main provisions of the heat power and aerodynamic calculation for the standard size range of such plants. Based on the results of experimental studies, a number of functional dependencies were obtained that characterize the operating modes of the plant. They determined the value of the heat transfer coefficient from the heat accumulating core to the circulating air depending on the coolant flow rate α = f(G). They presented the technical characteristic of the combined electrical unit current sample.